Solve the equation for x with elaborate steps, $(2x - 1)(x + 3) = 0$.
Answer
Verified
443.7k+ views
Hint: There are various ways which one might use to solve an equation, but first one needs to identify the highest power of the variable to be found in the equation. In this equation, we cannot directly find the highest power of x. Multiply the expressions to get a single line expression on the LHS. Proceed to the solution accordingly.
Complete step-by-step solution:
In the question we can see that there is no clarity on the highest power of the variable, x.
Hence, we use the BODMAS rule to open the brackets and multiply the contents with each other.
The LHS changes and the equation becomes,
$
(2x - 1)(x + 3) = 0 \\
\Rightarrow 2x \times x - 1 \times x + 3 \times 2x - 1 \times 3 = 0 \\
\Rightarrow 2{x^2} - x + 6x - 3 = 0 \\
\Rightarrow 2{x^2} + 5x - 3 = 0 \\
$
Thus, we see that the highest power of x is 2, which makes the equation a quadratic equation.
Now, we know that $x \times y = 0$ means that x and y both individually equate to zero.
So, from the question,
$(2x - 1) = 0,(x + 3) = 0$
$ \Rightarrow 2x = 1,x = - 3$
$ \Rightarrow x = \dfrac{1}{2},x = - 3$
Note: Mid-term factorization or completing square methods often become cumbersome and are time taking to solve. Whenever dealing with fractional or imaginary values, use of the quadratic formula to solve quadratic equations is recommended. The quadratic formula is $x = \frac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$ where a is the coefficient of ${x^2}$, b is the coefficient of x and c is the constant from the standard quadratic equation, $a{x^2} + bx + c = 0$.
Complete step-by-step solution:
In the question we can see that there is no clarity on the highest power of the variable, x.
Hence, we use the BODMAS rule to open the brackets and multiply the contents with each other.
The LHS changes and the equation becomes,
$
(2x - 1)(x + 3) = 0 \\
\Rightarrow 2x \times x - 1 \times x + 3 \times 2x - 1 \times 3 = 0 \\
\Rightarrow 2{x^2} - x + 6x - 3 = 0 \\
\Rightarrow 2{x^2} + 5x - 3 = 0 \\
$
Thus, we see that the highest power of x is 2, which makes the equation a quadratic equation.
Now, we know that $x \times y = 0$ means that x and y both individually equate to zero.
So, from the question,
$(2x - 1) = 0,(x + 3) = 0$
$ \Rightarrow 2x = 1,x = - 3$
$ \Rightarrow x = \dfrac{1}{2},x = - 3$
Note: Mid-term factorization or completing square methods often become cumbersome and are time taking to solve. Whenever dealing with fractional or imaginary values, use of the quadratic formula to solve quadratic equations is recommended. The quadratic formula is $x = \frac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}$ where a is the coefficient of ${x^2}$, b is the coefficient of x and c is the constant from the standard quadratic equation, $a{x^2} + bx + c = 0$.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE